The reality of using the job description in Libyan hospitals, "A field study on Al-Jalaa Accident Hospital in Benghazi” - إجبارة زينب; المطردي أمل; الكوافي وداد (Dirasat in Economics and Business, 2024)
This study aims to determine the reality of using the job description at Al-Jalaa Accident Hospital in the city of Benghazi, by identifying the level of support and awareness of the top management for the job description, and the availability of correct procedures for the job description, as well as reaching the level of using the job description when selecting, appointing and training workers, also identifying the extent to which job descriptions are used for evaluating employees’ performance when promoting and transferring. To achieve the objectives of the study, the researchers followed the 0descriptive approach, and a simple random sample of (196) individual workers was chosen, the study reached several results, the most important of which are: The level of using the job descriptions among the study sample was a moderate degree, the top management’s support and awareness of the job description was at a moderate level, and the level of using the job description when selecting, appointing and training.